2008
DOI: 10.1210/en.2008-0231
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Kisspeptin-54 Release Occurs with the Pubertal Increase in Luteinizing Hormone-Releasing Hormone-1 Release in the Stalk-Median Eminence of Female Rhesus Monkeys in Vivo

Abstract: The G-protein coupled receptor GPR54 and its ligand, KiSS-1-derived peptide kisspeptin-54, appear to play an important role in the mechanism of puberty. This study measures the release of kisspeptin-54 in the stalk-median eminence (S-ME) during puberty and examines its potential role in the pubertal increase in LHRH-1 release in female rhesus monkeys. First, developmental changes in release of kisspeptin-54 and LHRH-1 were assessed in push-pull perfusate samples obtained from the S-ME of prepubertal, early pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
178
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(191 citation statements)
references
References 35 publications
11
178
1
1
Order By: Relevance
“…Inhibition of hypothalamic kisspeptin signaling suppresses pulsatile GnRH/LH secretion (24,25). Kisspeptin levels were episodic and temporally coincided with or preceded GnRH pulses (20,37,38). However, the mechanism by which synchronous gene expression occurs in kisspeptin-stimulated GnRH neurons remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of hypothalamic kisspeptin signaling suppresses pulsatile GnRH/LH secretion (24,25). Kisspeptin levels were episodic and temporally coincided with or preceded GnRH pulses (20,37,38). However, the mechanism by which synchronous gene expression occurs in kisspeptin-stimulated GnRH neurons remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Kisspeptin-producing cells reside in two distinct hypothalamic regions, the anteroventral periventricular nucleus and the arcuate nucleus, and extend their neurites adjacent to axon terminals and cell bodies of GnRH neurons (15,18). Notably, kisspeptin release in the stalk-median eminence is pulsatile and exhibits a strong correlation with GnRH pulses (20). Furthermore, pulsatile kisspeptin administration drives gonadotropin secretion in juvenile male monkeys primed with GnRH.…”
mentioning
confidence: 99%
“…This role has been substantiated by compelling expression and functional data obtained in primates that support the important contribution of Kiss1 pathways in puberty. Thus, hypothalamic Kiss1 mRNA expression has been shown to increase during pubertal maturation in monkeys (100), a period when there is a rise in the pulsatile release of kisspeptin-54 in the median eminence of this species, which closely correlates with the enhancement of GnRH pulse frequency during this age (101). Moreover, repeated injections of kisspeptin-10 to monkeys at the end of the juvenile phase evoked a pattern of GnRH discharges similar to that seen at puberty (102), whereas kisspeptin antagonism suppressed GnRH secretion in prepubertal and pubertal monkeys (103).…”
Section: Role Of Nesfatin-1 In Puberty Onset: Supporting Evidencementioning
confidence: 99%
“…In addition, in the present study, we found that with the microdialysis method we were able to measure pulsatile LHRH release and to observe an increase in LHRH release in response to LHRH agonist challenge. A preliminary study in this lab also indicated that kisspeptin-54 (molecular weight: 5848) can be measured by the microdialysis method with the PAES membrane (Keen et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Although in the present study we did not measure small amino acid neurotransmitters, catecholamines and their metabolites, they should be easily assessed, as their molecular size is relatively smaller and unlike neuropeptides they are not sticky. Moreover, the advent of improved microdialysis membrane materials, such as PAES, is increasing the utility of the approach in measuring larger hypothalamic neuropeptides, such as kisspeptin-54 (Keen et al, 2007). While the push-pull perfusion method offers certain advantages, the microdialysis method can be highly desirable because of a significantly shorter time of chairing in non-human primates.…”
Section: Discussionmentioning
confidence: 99%